ATTITUDE AND REASONS TO THE BIRTH OF BOYS IN UZBEK FAMILIES - Khojikulov Naimjon Raimovich (American Journals, 2023)
In this article, the continuation of generations among the peoples of the world and the development of the material and cultural worldviews of many peoples over the centuries, parental love is also the result of a long and conflicting historical development, attitudes and reasons for the birth of a son in Uzbek families, scientific It is covered on the basis of literature and social surveys and comparative analysis with other nations.
Keywords: Nations, generations, child, family, future, parents, gender, boy, traditionality, custom.